2021
DOI: 10.3389/fchem.2021.630969
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Reactive Oxygen Species Generated by Inorganic Nanomaterials for Cancer Therapeutics

Abstract: Recently, inorganic nanomaterials have received considerable attention for use in biomedical applications owing to their unique physicochemical properties based on their shapes, sizes, and surface characteristics. Photodynamic therapy (PDT), sonodynamic therapy (SDT), and chemical dynamic therapy (CDT), which are cancer therapeutics mediated by reactive oxygen species (ROS), have the potential to significantly enhance the therapeutic precision and efficacy for cancer. To facilitate cancer therapeutics, numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…However, it is also expected that smaller NPs possess a higher surface area and thus have a higher concentration of active sites and structural defects. 88,89 Consequently, the reactivity of smaller NPs can be anticipated to be more than the larger ones. Recently, the anticancer properties of Se NPs have been reported by other researchers also and several mechanisms have been suggested for the same, including apoptosis, cell cycle arrest, interruption of the cell signaling pathway or some other ROS (reactive oxygen species)-mediated route.…”
Section: Similar Results Were Obtained In the Raman Mapping Measureme...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also expected that smaller NPs possess a higher surface area and thus have a higher concentration of active sites and structural defects. 88,89 Consequently, the reactivity of smaller NPs can be anticipated to be more than the larger ones. Recently, the anticancer properties of Se NPs have been reported by other researchers also and several mechanisms have been suggested for the same, including apoptosis, cell cycle arrest, interruption of the cell signaling pathway or some other ROS (reactive oxygen species)-mediated route.…”
Section: Similar Results Were Obtained In the Raman Mapping Measureme...mentioning
confidence: 99%
“…Apparently, the anticancer efficacy of Se NPs increased with decreasing particle size. ,, The probable reason might be the better cellular uptake in case of NPs with smaller dimensions, as has been reported in literature. However, it is also expected that smaller NPs possess a higher surface area and thus have a higher concentration of active sites and structural defects. , Consequently, the reactivity of smaller NPs can be anticipated to be more than the larger ones. Recently, the anticancer properties of Se NPs have been reported by other researchers also and several mechanisms have been suggested for the same, including apoptosis, cell cycle arrest, interruption of the cell signaling pathway or some other ROS (reactive oxygen species)-mediated route. ,, It is therefore highly likely that these mechanisms could be more effective in the presence of smaller NPs than larger ones.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[18] Moreover, it has been shown that FCDs can produce ROS upon photoexcitation owning to the band-edge defect effect and that the photosensitization performance of FCDs is also dependent on the surface functionalization and irradiation source. [19] Thus the superoxide indicator dihydroethidium (DHE, for which a decrease in fluorescence on oxidation indicates ROS production) was used to monitor ROS formation in LED and FCD treated bacteria. For both E. coli and S. aureus the fluorescence intensity of DHE for FCD-incubated (200 µg/mL) bacteria after 90 minutes of LED illumination was significantly lower (by 46% compared to DHE controls) than that of cultures treated with FCDs but in the absence of LED illumination (t-test p = 0.0007 and p = 0.0008 respectively) (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic nanomaterials have unique optical, electrical, and magnetic properties. Therefore, they usually have the effect of photothermal therapy (PTT) and photodynamic therapy (PDT) in tumor immunotherapy (131), which is a suitable drug carrier as well as tumor therapeutic agent. Zhang et al developed a new type of gold nanoparticle (AuNP) for tumor photothermal and immunotherapy.…”
Section: Targeted Drug Delivery System Based On Nanomaterialsmentioning
confidence: 99%